Designing an expert system for determining student learning styles using forward chaining in engineering education - Muhammad Anwar (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
Engineering education prepares its graduates able to work in the community and entrepreneurship, the quality of graduates is highly determined by the quality of the learning process is no exception for student learning styles. The purpose of this study was to describe the design of the expert system to determine the student learning style, the method used was forward chaining. The results of the design of this application have been able to diagnose student learning styles efficiently and provide the best solutions for their learning.